Anatomical distribution of areas of preserved cartilage in advanced femorotibial osteoarthritis using CT arthrography (Part 1). Issue 1 (January 2015) - Omoumi, P.; Michoux, N.; Thienpont, E.; Roemer, F.W.; Vande Berg, B.C.
Summary: Objective: To determine subregions of normal and abnormal cartilage in advanced stages of femorotibial osteoarthritis (OA) by mapping the entire femorotibial joint in a cohort of pre-total knee replacement (TKR) OA knees. Design: We defined an areal subdivision of the femorotibial articular cartilage surface on CT arthrography (CTA), allowing the division of the femorotibial articular surface into multiple (up to n = 204 per knee) subregions and the comparison of the same areas between different knees. Two readers independently classified each cartilage area as normal, abnormal or non-assessable in 41 consecutive pre-TKR OA knees. Results: A total of 6447 cartilage areas (from 41 knees) were considered assessable by both readers. The average proportion of preserved cartilage was lower in the medial femorotibial joint than in the lateral femorotibial joint for both readers (32.0/69.8% and 33.9/68.5% (medial/lateral) for reader 1 and 2 respectively, all P < 0.001). High frequencies of normal cartilage were observed at the posterior aspect of the medial condyle (up to 89%), and the anterior aspect of the lateral femorotibial compartment (up to 100%). The posterior aspect of the medial condyle was the area that most frequently exhibited preserved cartilage in the medial femorotibial joint, contrasting with the high frequency of cartilage lesions in the rest of that compartment. Conclusions: Cartilage at the posterior aspect of the medial condyle, and at the anterior aspect of the lateral femorotibial compartment, may be frequently preserved in advanced grades of OA.